Post-therapeutic detection of local tumor persistence of head and neck cancer: the value of routine control endoscopy with biopsy and medical imaging - Engert, Tobias; Acu, Leyla; Schoenhofer, Johann; Rommers, Nikki; Ahmad, Nader (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Insufficient local tumor control is the main cause of treatment failure in head and neck cancer (HNC). Re-staging HNC is challenging because of post-therapeutic tissue distortion. We investigate whether medical imaging and biopsy is more sensitive in identifying tumor persistence. Methods: In our clinic a re-staging with a control endoscopy and medical imaging is performed 3 months after therapy for some HNC patients. In this retrospective study, we compare the accuracy of imaging to the histology (gold standard). Imaging reports were classified according to 3 scales and re-assessed by 2 neuroradiologists. Furthermore, we evaluate recurrence rates and disease-free survival. Results: 100 cases were evaluated. 14 patients presented with positive histology at the re-staging. Biopsy detected malignancy in 7 patients with inconspicuous imaging. Disease-free survival during the first 2 years was generally low (n=55). The accuracy of the RECIST scale was 0.74 with a sensitivity of 0.50 and a specificity of 0.78. Imaging reports reviewed according to the Lee-scale and a self-developed scale presented an accuracy of 0.47 and 0.51. Re-assessment of imaging by 2 neuroradiologists showed an accuracy of 0.87. Conclusions: Medical imaging alone serves as a moderate diagnostic tool to diagnose local persistence of HNC 3 months after therapy. Radiologic misdiagnosing can be addressed by control endoscopy. Our results indicate a benefit of routine biopsies since reliance on imaging may fail to notice tumor persistence. A binary classification of imaging showed a higher accuracy than conventional imaging scales and may help to predict tumor recurrence within 24 months after re-staging.